Settlement of Default Debtors on Amitra Financing (Hajj and Umrah) in Limited Liability Companies (Fif Group) Prapat Regional Branch - Retni Ayu Syafitri; Elviana Sagala; Sriono Sriono; Risdalina Risdalina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Limited Liability Company Federal international finance group is a finance company that provides conventional and sharia financing facilities. And one of the financing that is engaged in sharia is AMITRA. Amitra is one of the funds that has been regulated in accordance with the fatwas with the MUI national sharia and is supervised by the financial services authority. Amitra is sharia financing from the Fifgroup for Islamic Hajj, Umrah and gold financing, or even qurban and aqiqah submissions. In addition to federal international finance, there are also several finance companies that provide hajj and umrah financing, for example Adira, Bess finance, etc. So here the writer is interested in discussing the financing of Hajj and Umrah in federal international finance.